The Utilization of Instagram and Tiktok as Promotion Media for Native Papuan Entrepreneurs in Jayapura - El Shaddai Sandhy Pustap; Markus Setiawan Soumokil; Hendra Litamahaputty (Sean Institute, 2026)
Social media has become an effective marketing tool for Micro, Small, and Medium Enterprises (MSMEs). However, native Papuan entrepreneurs in Jayapura face challenges in promoting their local products due to limited digital literacy and internet access. This community service activity aimed to analyze and implement promotion strategies using Instagram and TikTok to increase the visibility of native Papuan businesses. The methods used included digital marketing training, creative content production based on local culture, and evaluation of social media engagement. The partners involved were